Efeito da idade no fenótipo em heterozigose para mutação nula no gene do receptor do hormônio liberador do GH - Pereira, Rossana Maria Cahino (2014)
Several recessive diseases present heterozygous phenotype. In Itabaianinha, Brazil, there is a big cohort with the homozygous mutation c.57 +1 G> A in the GHRH receptor (GHRHR) gene, leading to severe short stature. Previous study shows that heterozygous individuals (MUT/N) exhibit similar height, insulin like growth factor type 1 (IGF - I) and percentage of fat mass, but reduced weight, body mass index (BMI) and muscle mass. However, only 10 % of these were 60 or more years old. Moderate reduction in the GH/ IGF-I axis activity may have a greater impact on the aging period, when the activity of this axis naturally decreases. We question whether the study of heterozygosity for the mutation would result in a partial phenotype in the elderly cohort individuals. 843 individuals were analyzed in a cross sectional study by height, weight, systolic and diastolic blood pressure and BMI in two groups (young, 20-40 years of age) and old (60-80 years) of MUT/N individuals, and compared to a large number of individuals of normal genotype (N/N). SDS weight was lower [-0.13 (1.4) and -0.56 (1.8), p=0.03], and BMI had a trend toward reduction [0.08 (1.40) and 0.33 (1.4), p=0.060] in young MUT/N in comparison to young N/N. SDS height was lower in older MUT/N individual vs. N/N [-2.79 (1.1) and -2.37(1.0), p=0.04], corresponding to a reduction of 4.16 cm. We conclude the previous data reduction in weight and BMI in young and show reduced stature in older MUT/N subjects, suggesting different effects of heterozygosis through the ages. The reduction of muscle mass already present at young age, aggravated by aging may contribute to this reduction in height. Heterozygous GHRHR mutations may be a factor contributing to frailty in elderly.